Farmers land tenure arrangements and technical efficiency of growing crops in some selected upazilas of Bangladesh (Bangladesh Journal of Agricultural Research, 2015)
There are different land tenure arrangements in crop cultivation in Bangladesh. It is needed to detect how farmers could maximize the benefits from proper utilization of their resources and technologies in these prevailing different land tenure arrangements in crop cultivation. The main quest of this study is to analyze the actual production level and how much is deviated from maximum attainable production level in terms of technical efficiencybased on average gross revenue of output ha-1 in the cultivated various types of crops among different categories of farmers and identifies the impact of the factors associated with technical efficiency.In search of this research question a case study was conducted in two Upazilas (Sub districts) in Bangladesh based on cross section data. This data were collected from January to March, 2013. Age of the household head, education, farm size, off-farm income and other concerned issues were assessed. Maximum likelihood estimation and ordinary least square regression techniques were used to estimate the parameters of the stochastic production frontier.Ordinary least square regression was used to identify the factors associated with technical efficiency. The study reveals that the technical efficiency varied among different categories of farmers. But land rent (0.0575) and weed management (0.0838) had significant positive impact on technical efficiency. This detects the potentiality to improve the technical efficiency by taking proper measures in land tenure arrangements in consideration of land rent andprovide required weed management support for the farmers.Bangladesh J. Agril. Res. 40(3): 347-361, September 2015